Participatory Video for Women's Empowerment: Fostering Agency and Voice in Self-Help Groups - Chanana , Deepali; Paul , Pragati; Kusuma, Kusuma Sankar (IGNOU Journal of Media and Empowerment (ISSN: 3048-8478), 2025)
The study explores the use of participatory video as a transformative tool to empower women in Self-Help Groups (SHGs), amplify their voices, and foster community dialogue. Participatory video plays a crucial role in fostering communication, engaging community members and promoting advocacy and capacity building. The research examines the use of participatory video as a tool for storytelling and creating visibility and identity as social actors for women in self-help groups in Nizamuddin, Delhi. The study incorporated a three-day planned, intense collaborative workshop for SHG women to impart skills in video making, storytelling through mobile phones and local advocacy. Through the workshops, the research developed a collaborative environment for Sakhis (participants) to develop agency and the ability to voice their perspectives and catalyse dialogue within their communities. The participatory approach acts as a catalytic change for SHG women, increasing their agency to express and initiate the local changes. The study employed a Participatory Action Research (PAR) framework and investigated how mobile-based storytelling can serve as a medium for empowerment. Participatory video has proved to be an engaging and effective tool for women. In the context of adding the mobile and digital platforms, it has pushed the collaboration and creative narratives beyond their own community to the wider network of communities.